DEVELOPMENT OF TEACHING MATERIALS IN THE FORM OF E-MODULES CHARACTER BASED ON IPS EDUCATION IN ELEMENTARY SCHOOL - I Nyoman Karma; Nurhasanah; Husniati; Oktaviyanti, Itsna; Novitasari, Setiani (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
The purpose of this study is to develop teaching materials in the form of character-based elementary social studies education e-modules and to determine the feasibility of teaching materials in the form of character-based elementary social science education e-modules. This research uses R&D (Research and Development) research methods. The development of this e-module is devoted to Elementary Social Studies Education Courses. This is expected to help students understand the material in the Social Sciences Education course in SD. The stages in this research consist of three development steps, namely define, design, and develop. The data analysis technique for the feasibility of the character-based Elementary Social Studies Education e-module was carried out by making conclusions from the data obtained from the expert validators and the results of the student response questionnaire analysis. Data in the form of scores will be converted into qualitative data. The results showed that in the defined stage, it was done by analyzing learning problems, analyzing the characteristics of PGSD students and analyzing materials. The design stage includes compiling systematics, determining the title and finally compiling character-based material. The development stage seen from the expert validators shows that the E-Module gets a decent criterion with a score of 75%, after repairing the E-Modul gets a very decent criterion with a score of 86.2%. The results of student responses showed that the criteria were very feasible with a score of 89%, so there was no need for revision. Character-based Elementary Social Studies Education E-Modules get an average of very valid criteria so that the E-Modules that have been developed can be used in the PGSD study program after going through the revision of the E-Module ease of access.